Strand compositional asymmetry in bacterial and large viral genomes - Mrázek, Jan (The National Academy of Sciences, 1998)
Several bacterial genomes exhibit preference for G over C on the DNA leading strand extending from the origin of replication to the ter-region in the genomes of Escherichia coli, Mycoplasma genitalium, Bacillus subtilis, and marginally in Haemophilus influenzae, Mycoplasma pneumoniae, and Helicobacter pylori. Strand compositional asymmetry is not observed in the cyanobacterium Synechocystis sp. genome nor in the archaeal genomes of Methanococcus jannaschii, Methanobacterium thermoautotrophicum, and Archaeoglobus fulgidus. A strong strand compositional asymmetry is observed in β-type but not α- or γ-type human herpesviruses featuring G > C downstream of oriL and C > G upstream of oriL. Dinucleotide relative abundances (i.e., dinucleotide representations normalized by the component nucleotide frequencies) are consonant with respect to the leading and lagging strands. Strand compositional asymmetry may reflect on differences in replication synthesis of the leading versus lagging strand, on differences between template and coding strand associated with transcription-coupled repair mechanisms, on differences in gene density between the two strands, on differences in residue and codon biases in relation to gene function, expression level, or operon organization, or on differences in single or context-dependent base mutational rates. The absence of strand asymmetry in the archaeal genomes may reflect the presence of multiple origins of replication.